Short-term environmental enrichment induces ‘resilience to chronic stress’ in adulthood (A study traversing behavioural, neuronal and molecular plasticity in brain) - Kolikil, Archana Ashokan (2017)
In mammals, expression of fear is an adaptive trait that safeguards individuals from natural threats including predators. However, this expression can be exacerbated by chronic stress into manifestation of negative valence such as anxiety, leading to mental disorders. The potentiation of anxiety is primarily associated with neuronal changes in the basolateral amygdala (BLA). Stress-induced hyperactivation of BLA in the form of dendritic reorganisation corresponds to precipitation of anxiety-states in adult male rats. This study shows that short-term environmental enrichment (EE) in adulthood is sufficient to counter anxiety-related pathologies induced by chronic stress. Stressed subjects housed in EE show lowered anxiety in contrast to those housed in standard-conditions. They differ in dendritic reorganization in the form of lowered spine-density compared to their stressed counterparts without EE. Furthermore, compared to the latter, the EE-exposed stressed animals also differ in protein-expression of activated glucocorticoid-receptors, and pro - brain-derived neurotrophic factor, which play an important role in mediating stress-response. These observations suggest that short-term EE can potentially cultivate resilience in adulthood against stress-induced pathologies at behavioural, neuronal, and molecular levels.